Morphological Study of the Coronoid Process of Mandible in North Indian Population - Gaharwar, Anamika; Tewari, Vineeta (Academia Anatomica International, 2019)
Introduction: Morphological variations in coronoid process are produced by the corresponding developmental variations. The present study was conducted to assess morphological variations of coronoid process of mandible. Subjects and Methods: The present study was conducted in the department of Anatomy. It comprised of 100 subjects of both genders. All subjects were subjected to panoramic radiograph. The different shapes of coronoid process were compared. Results: Out of 100 subjects males were 50 and females were 50. Triangular shape coronoid process was seen in 32 males and 36 females, hook shaped in 14 males and 8 females and rounded shaped in 4 males and 6 females. The difference was non- significant (P> 0.05). On left side triangular shape was seen in 33 and 35 on right side, hook form was seen in 10 in left side and 7 in right side and rounded was seen 7 in left side and 8 in right side. The difference was non-significant (P> 0.05). Conclusion: Authors found variation in shape of coronoid process. Most common type was triangular followed by hook variety.